Chemical exchange saturation transfer (CEST) signal intensity at 7T MRI of WHO IV° gliomas is dependent on the anatomic location. Issue 3 (22nd August 2018) - Dreher, Constantin; Oberhollenzer, Johanna; Meissner, Jan‐Eric; Windschuh, Johannes; Schuenke, Patrick; Regnery, Sebastian; Sahm, Felix; Bickelhaupt, Sebastian; Bendszus, Martin; Wick, Wolfgang; Unterberg, Andreas; Zaiss, Moritz; et al.
Abstract : Background: Chemical exchange saturation transfer (CEST) is a novel MRI technique applied to brain tumor patients. Purpose: To investigate the anatomic location dependence of CEST MRI obtained at 7T and histopathological/molecular parameters in WHO IV° glioma patients. Study Type: Analytic prospective study. Population: Twenty‐one patients with newly diagnosed WHO IV° gliomas were studied prior to surgery; 11 healthy volunteers were investigated. Field Strength/Sequence: Conventional MRI (contrast‐enhanced, T2 w and diffusion‐weighted imaging) at 3T and T2 w and CEST MRI at 7T was performed for patients and both patients and volunteers. Assessment: Mean CEST signal intensities (nuclear‐Overhauser‐enhancement [NOE], amide‐proton‐transfer [APT], downfield NOE‐suppressed APT [dns‐APT]), ADC values, and histopathological/molecular parameters were evaluated with regard to hemisphere location and contact with the subventricular zone. CEST signal intensities of cerebral tissue of healthy volunteers were evaluated with regard to hemisphere discrimination. Statistical Tests: Spearman correlation, Mann–Whitney U ‐test, Wilcoxon signed‐rank‐test, Fisher's exact test, and area under the receiver operating curve. Results: Maximum APT and dns‐APT signal intensities were significantly different in right vs. left hemisphere gliomas ( P = 0.037 and P = 0.007), but not in right vs. left hemisphere cerebral tissue of healthy subjects ( P = 0.062‐0.859). Mean ADC values were significantly decreased in right vs. left hemisphere gliomas ( P = 0.044). Mean NOE signal intensity did not differ significantly between gliomas of either hemisphere ( P = 0.820), but in case of subventricular zone contact ( P = 0.047). A significant correlation was observed between APT and dns‐APT and ADC signal intensities (rs = –0.627, P = 0.004 and rs = –0.534, P = 0.019), but not between NOE and ADC (rs = –0.341, P = 0.154). Histopathological/molecular parameters were not significantly different concerning the tumor location ( P = 0.104–1.000, P = 0.286–0.696). Data Conclusion: APT, dns‐APT, and ADC were inversely correlated and depended on the gliomas' hemisphere location. NOE showed significant dependence on subventricular zone contact. Location dependency of APT‐ and NOE‐mediated CEST effects should be considered in clinical investigations of CEST MRI. Level of Evidence: 2 Technical Efficacy: Stage 3 J. Magn. Reson. Imaging 2019;49:777–785.